2021
DOI: 10.2147/ijgm.s317405
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Immune Infiltration and the Key Immune-Related Genes in Acute Type A Aortic Dissection in Bioinformatics Analyses

Abstract: Background Immune-inflammatory mechanisms contribute greatly to the complex process leading to type A aortic dissection (TAAD). This study aims to explore immune infiltration and key immune-related genes in acute TAAD. Methods ImmuCellAI algorithm was applied to analyze patterns of immune infiltration in TAAD samples and normal aortic vessel samples in the GSE153434 dataset. Differentially expressed genes (DEGs) were screened. Immune-related genes were obtained from ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 55 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…Interestingly, our study found low abundance of γδT cells in aortic dissection vessel tissue. This is in accordance with several other studies which also found low levels of γδT cells, although some were not statistically significant [ 20 23 ]. We think the cause may be as follows.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our study found low abundance of γδT cells in aortic dissection vessel tissue. This is in accordance with several other studies which also found low levels of γδT cells, although some were not statistically significant [ 20 23 ]. We think the cause may be as follows.…”
Section: Discussionsupporting
confidence: 93%
“…5,6 Despite the advances in surgical techniques and perioperative management, the in-hospital mortality rate of Stanford type A AD patients remains high. [7][8][9] Recently, some prognostic factors have been identified to predict the in-hospital survival of Stanford type A AD patients, 10,11 while discovering more potential AD biomarkers is still necessary and remains a critical issue for clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…However, a cluster of Th17-like T cells was found to expand in the AD group. Previous studies also reported elevation of Th17 cells both in AD tissues and blood samples of AD patients ( 50 , 51 ). Ju et al ( 52 ) observed Th17-cell accumulation in both patients and mouse models of aortic dissection.…”
Section: Discussionmentioning
confidence: 59%